Chilean lawmakers want ‘museum of truth’ to provide far-right take on Allende era - Bartlett, John (The Guardian, 2026)
National Libertarian party wants museum to highlight ‘victims’ of socialist government ousted by CIA-backed coup in 1973
Chile
Keywords: Augusto Pinochet; Chile; World news